2019
DOI: 10.1111/1462-2920.14863
|View full text |Cite
|
Sign up to set email alerts
|

Subpopulations of hyphae secrete proteins or resist heat stress in Aspergillus oryzae colonies

Abstract: Hyphae at the outer part of colonies of Aspergillus niger and Aspergillus oryzae are heterogeneous with respect to transcriptional and translational activity. This heterogeneity is maintained by Woronin body mediated closure of septal pores that block interhyphal mixing of cytoplasm. Indeed, heterogeneity between hyphae is abolished in ΔhexA strains that lack Woronin bodies. The subpopulation of hyphae with high transcriptional and translational activity secretes enzymes that degrade the substrate resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Although A. oryzae SSC has been widely utilized in fermentation and brewing industries, cellular and physiological studies on A. oryzae SSC have not yet been conducted well. Recently, it was revealed that transcriptional and translational heterogeneity in multicellular A. oryzae cells is related to protein secretion in stress responses [ 137 ]. Moreover, it was shown that under stress conditions, stress granules that consist of non-translating messenger ribonucleoproteins are formed around the hyphal tip region of A. oryzae cells [ 138 ], although the underlying molecular and physiological details of stress granule formation need further analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Although A. oryzae SSC has been widely utilized in fermentation and brewing industries, cellular and physiological studies on A. oryzae SSC have not yet been conducted well. Recently, it was revealed that transcriptional and translational heterogeneity in multicellular A. oryzae cells is related to protein secretion in stress responses [ 137 ]. Moreover, it was shown that under stress conditions, stress granules that consist of non-translating messenger ribonucleoproteins are formed around the hyphal tip region of A. oryzae cells [ 138 ], although the underlying molecular and physiological details of stress granule formation need further analyses.…”
Section: Discussionmentioning
confidence: 99%
“…By plugging the pores, intercompartmental and interhyphal cytoplasmic mixing is interrupted (Bleichrodt et al 2012(Bleichrodt et al , 2015a. Intact growing hyphae of Aspergillus oryzae (Bleichrodt et al 2012), Aspergillus niger (Tegelaar et al 2019), and Zymoseptoria tritici (2017b) plug their pores with Woronin bodies, while hyphae of the basidiomycete Schizophyllum commune close their pores with the septal pore cap (van Peer et al 2010). Environmental conditions impact incidence of septal closure in S. commune (van Peer et al 2009), A. oryzae and A. niger (Tegelaar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Intact growing hyphae of Aspergillus oryzae (Bleichrodt et al 2012), Aspergillus niger (Tegelaar et al 2019), and Zymoseptoria tritici (2017b) plug their pores with Woronin bodies, while hyphae of the basidiomycete Schizophyllum commune close their pores with the septal pore cap (van Peer et al 2010). Environmental conditions impact incidence of septal closure in S. commune (van Peer et al 2009), A. oryzae and A. niger (Tegelaar et al 2019). Low glucose levels reduce plugging incidence in S. commune, while presence of antibiotics, heat shock, and hypertonic shock promote septal closure (van Peer et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germination of conidia initiates the colonization of the substrate resulting in an interconnected hyphal network called mycelium (Adams et al, 1998). Hyphae in the mycelium specialize by forming secretion hyphae, resistor hyphae and aerial hyphae Tegelaar et al, 2020). Both thin and wide aerial hyphae are distinguished.…”
Section: General Introductionmentioning
confidence: 99%